Governance and implementation of solar-powered digital health systems in low- and middle-income countries: a mixed-methods study from Kenya and Ethiopia - Ronald Danny Nyatuka; Mohammad Sakikhales; Pazion Cherinet; Md Shafiqur Rahman Jabin (Frontiers in Digital Health, 2026)
Background Digital health systems are increasingly recognised as critical components of health system strengthening in low- and middle-income countries (LMICs). However, their effectiveness is often constrained by unreliable energy infrastructure, weak governance, and fragmented implementation approaches. Solar-powered digital health systems offer a promising solution, but their scalability depends on integrated governance and sustainable implementation models. Objective This study aimed to develop a governance and implementation framework for scaling solar-powered digital health systems in LMICs, using empirical evidence from Kenya and Ethiopia. Methods A mixed-methods study was conducted across selected rural and peri-urban health facilities in Kenya and Ethiopia. Data sources included facility-level infrastructure assessments, key informant interviews with health system stakeholders, and a multi-sectoral validation workshop. Quantitative data were analysed descriptively, while qualitative data were analysed using thematic analysis to indicate governance, coordination, and implementation dimensions. Findings were synthesised into a policy-oriented framework. Results The study emerged from a hybrid governance model combining national-level policy oversight with decentralised implementation as critical for scalability. Cross-sector coordination, facilitated through a Joint Technical Steering Committee, emerged as essential for aligning health, energy, and information and communication technology (ICT) actors. A phased implementation pathway was developed, incorporating facility readiness assessment, system deployment, interoperability, and lifecycle-oriented maintenance supported by public–private partnerships and blended financing mechanisms. The findings highlight the importance of integrating energy infrastructure into digital health governance to ensure system functionality and sustainability. Conclusions Solar-powered digital health systems can strengthen health service delivery in resource-constrained settings, but require coordinated governance, sustainable financing, and structured implementation strategies. The proposed framework advances an integrated energy–digital health governance nexus, offering a practical and conceptual pathway for scaling resilient digital health infrastructure in LMICs. Policymakers should prioritise cross-sector collaboration and system-level integration to move beyond pilot-driven approaches and achieve sustainable impact.